The Supreme Court compendium : two centuries of data, decisions, and developments /: two centuries of data, decisions, and developments. (2021) - Epstein, Lee, 1958-; Segal, Jeffrey Allan; Spaeth, Harold J; Walker, Thomas G, 1945-
No abstract available